Struktura organów władzy Republiki Kuby na podstawie ustawy zasadniczej - Debita, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The article is about to analyze and present the structure of the authorities of the Republic of Cuba and their powers under the Constitution of the state. The Basic Law was adopted in 1976 and was amended in the years 1992, 1993 and 2002. As indicated in the Preamble to the Constitution, the state system is based on Marxist and Leninist models in conjunction with the Latin American tradition and the specific historical circumstances in which it was endowed.It is worth noting the fact that in Polish literature this subject is not too extensively described – last mention on Cuban constitution came in 1992, so it do not include all the amendments. For this reason, the author reach to the foreign sources and refers to the official websites of the Cuban government and the Cuban political blogs.
Keywords: Structure of the authorities; Republik of Cuba; Constitucion; Cuba